The layers of the IT Agreement's trade impact - Christian Henn; Arevik Gnutzmann-Mkrtchyan (World Trade Organization (WTO), 2015)
The WTO's plurilateral Information Technology Agreement (ITA) reduced tariffs to zero on many IT products. This paper presents a comprehensive study of its trade impacts by incorporating recent insights from both the global value chain (GVC) and time in trade literatures. Inserting tariffs directly into the gravity equation breaks the ITAs impact down into four layers. Import demand elasticities are found to be non-linear: Tariff reduction (layer 1) has relatively small impacts, while complete tariff elimination (layer 2) has high impacts, especially for intermediate goods. Beyond that, ITA accession has positive non-tariff effects on both imports (layer 3) and exports (layer 4). These commitment effects suggest that higher trade policy certainty affects investment and sourcing decisions in favour of signatories: Their ITA exports performed better relative to other ICT and machinery exports, unlike non-members. But "passive signatories" - which joined mainly as a by-product of a larger policy objective - reaped the most benefits. Featuring a smaller ITA sector upon accession, their final good exports increased also in absolute terms due to downstream GVC integration. However, such impacts are strongly heterogeneous with respect to countries' geographical remoteness, education levels, business environment and institutions. China stands out with especially strong post-accession export increases, also extending to intermediate goods.
Keywords: F13; F14; L63; 330; tariffs; trade policy certainty; value chains; fragmentation; WTO Information Technology Agreement; gravity equation; product-level trade; non-linearity